ANALYSIS OF FEE ACCOUNTING INFORMATION SYSTEMS LECTURE AT ITB AAS INDONESIA IN THE PANDEMIC TIME OF COVID-19 - Muqorobin Muqorobin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to identify and analyze accounting information systems Flow of Tuition Fee Payment during the Covid-19 Pandemic at the University of Technology Sumbawa. The method used in this research is descriptive method qualitative. The sources of this research included the Vice Chancellor for 2 Fields Finance, to be precise, the Directorate of Financial Administration, University of Technology, Sumbawa. Employees who become informants in this study are Finance Director, Treasurer University, and Sub Directorate of Financial Administration. The data source of this research are primary and secondary, with data collection methods using techniques interviews, documentation and observation. The results of this study indicate that Accounting Information System for Tuition Fee Payment Flow during the Covid-19 Pandemic The Sumbawa University of Technology has been carried out effectively and efficiently. That matter can be seen based on existing data, procedures, infrastructure and software as well responsible and competent human resources. With the Groove you can pay online tuition fees during the Covid-19 pandemic help Sub. The Directorate of Financial Administration works while still doing social distancing so that the payment flow can be applied to date.